Dry eye disease and spondyloarthritis: expanding the spectrum of systemic inflammatory disorders associated with ocular surface disease. Data from the international AIDA Network Spondyloarthritis Registry - Vitale, Antonio; Caggiano, Valeria; Martín-Nares, Eduardo; Di Meglio, Nunzia; Sica, Cristian; Hinojosa-Azaola, Andrea; Perfetti, Maria Orsetta; Pagliara, Alessandra; Guidetti, Giorgia; Fonollosa, Alex; Lopez, Roberta; Sbalchiero, Jessica; et al. (Frontiers in Medicine, 2024)
Objective Dry eye disease (DED) is a condition associated with a myriad of systemic disorders. According to recent preliminary data, axial spondylarthritis (axial-SpA) could represent a new entity associated with DED. Therefore, this study aimed to assess DED in patients with axial SpA by performing quantitative and qualitative specific tests to investigate the potential association between DED and ocular surface damage in patients with axial-SpA and to identify potential variables associated with DED. Methods A total of 71 patients with axial-SpA who fulfilled the Assessment of SpondyloArthritis International Society (ASAS) classification criteria and 19 healthy controls were enrolled in this study. Both the patients and the controls underwent a complete ocular assessment aimed at evaluating the tear film and ocular surface, which included the Schirmer test, tear break-up time (TBUT), fluorescein staining, and lissamine green staining. The Ocular Surface Disease Index (OSDI) questionnaire was administered to all patients. Results DED symptoms were reported in 46 (64.8%) patients and three (15.8%) healthy controls (p = 0.0004). The odds ratio for receiving a diagnosis of axial-SpA based on the presence of dry-eye-related symptoms was 9.2 (95% C.I. 2.72–42.52, p = 0.001). The Schirmer test values of < 6 mm/5 min were observed in 31 (43.7%) patients with axial-SpA and two (10.5%) healthy controls (p = 0.013); a TBUT of <5 s was observed in 34 (47.9%) patients with axial-SpA and six (31.6%) healthy controls. The median OSDI score was found to be 22.9 (IQR = 29.35) among the patients with axial-SpA and 0.0 (IQR = 4.69) among the healthy controls (p = 0.009). The fluorescein and lissamine green staining of the ocular surface indicated a significantly higher Oxford Grading Scale in the patients with axial-SpA than in the healthy controls. Conclusion Patients with axial-SpA often complain of eye dryness, which may be quantified with the self-administered OSDI questionnaire and objectively assessed through the tests commonly used for the diagnosis of DED. Patients suspected of having axial-SpA should routinely be asked about dry eye symptoms and evaluated for potential corneal and conjunctival damage.